Relación entre el gasto de capital y la rentabilidad del Banco Pichincha en Perú durante el periodo 2017 – 2024 - Zagaceta Perea, July Solanghyel (2025)
This research analyzes the relationship between capital expenditure (CAPEX) and the financial profitability of Banco Pichincha during the period 2017-2024. Using a quantitative approach based on Spearman’s correlation, the study examines the interactions between CAPEX and various financial indicators, including gross financial margin, net margin, ROA, and net income. The results reveal a positive and significant relationship between capital expenditure and overall bank profitability, with a correlation coefficient of 0.9428 (p = 0.0048), confirming that investments in infrastructure and technology have contributed to improved financial performance. However, the relationship between CAPEX and the gross financial margin was not statistically significant, suggesting that operational profitability is influenced by other factors such as credit placement strategies and cost structures. Additionally, liquidity and capitalization showed moderate effects on profitability but lacked conclusive statistical significance. The findings reinforce the importance of a strategic approach to capital investment, combined with income optimization and financing policies. An integrated strategy is recommended to ensure the bank’s long-term financial sustainability.